HUBUNGAN ANTARA WORK LIFE BALANCE DENGAN KEPUASAN KERJA PADA KARYAWAN SALES - Sarah Ancella Rudfika Wirawan; Sukmarani (Faculty of Psychology, Atma Jaya Catholic University of Indonesia, 2023)
Work life balance is a situation where employees can balance their work or work with other commitments through the freedom to use their working hours. One of the benefits of employees having a work life balance is increasing physical health, mental health and increasing job satisfaction. However, it turns out that most people when they enter the world of work lose balance in their lives. the results of interviews conducted by one of the researchers with several sales, so high the targets or demands as salesperson make them have to work hard even outside working hours so that they arereluctant to work and feel burdened by the responsibilities that have been assigned. This study aims to find out and analyze the relationship between the demands dimension and the resources dimension of work life balance with job satisfaction in sales. The sampling technique in this study was accidental sampling. This study uses a correlational quantitative research approach. Data was obtained from 195 salespeople who are domiciled in Indonesia using Fisher's (2009) WLB scale measurement tool adapted by Gunawan et al. (2019) and Spector's JSS (1997) which was adapted by Zulfikar (2016). The results showed that there was a significant negative relationship between demands and job satisfaction (r = -0.520; p = 0.000) and there was a strong positive significant relationship between the resourcesdimension and job satisfaction (r = 0.334 and p = 0.000). Further research results will be discussed in the research discussion.